2008
DOI: 10.1111/j.1469-8137.2008.02450.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of synchronicity between host phenology and pathogen activity in the distribution of sudden oak death canker disease

Abstract: Summary• Variations in synchronicity between colonization rate by the pathogen and host phenology may account for unexplained spatial distribution of canker disease. The hypothesis that synchronous pathogenicity and host development are necessary for incidence of sudden oak death disease was tested by correlating seasonal variations in host cambial phenology and response to inoculation with Phytophthora ramorum.• Response to infection was estimated by inoculating branch cuttings from coast live oak (Quercus ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…Based on epidemiological studies, vaccination programs are performed on seasonal bases to reduce the incidence of human influenza and other diseases. The incidence and spatial distribution of canker disease in oak trees has been attributed to the need for synchronicity of pathogen activity and seasonal host development (Dodd et al, 2008). The peak of sporulation by Phytophtora ramorum and Fusarium circinatum, the casual agents of sudden oak death canker disease and pine pitch canker, respectively, is when the climate is cool and humid (Schweigkofler et al, 2004;Dodd et al, 2008).…”
Section: Developmental Stage Of the Hostmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on epidemiological studies, vaccination programs are performed on seasonal bases to reduce the incidence of human influenza and other diseases. The incidence and spatial distribution of canker disease in oak trees has been attributed to the need for synchronicity of pathogen activity and seasonal host development (Dodd et al, 2008). The peak of sporulation by Phytophtora ramorum and Fusarium circinatum, the casual agents of sudden oak death canker disease and pine pitch canker, respectively, is when the climate is cool and humid (Schweigkofler et al, 2004;Dodd et al, 2008).…”
Section: Developmental Stage Of the Hostmentioning
confidence: 99%
“…The incidence and spatial distribution of canker disease in oak trees has been attributed to the need for synchronicity of pathogen activity and seasonal host development (Dodd et al, 2008). The peak of sporulation by Phytophtora ramorum and Fusarium circinatum, the casual agents of sudden oak death canker disease and pine pitch canker, respectively, is when the climate is cool and humid (Schweigkofler et al, 2004;Dodd et al, 2008). Dodd et al (2008) demonstrated that the development of sudden oak death canker disease required coincidence of pathogen sporulation and activity of the host cambial tissue, and they found a strong correlation between date of largest lesion size and timing of spring bud burst.…”
Section: Developmental Stage Of the Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change could make forests on the West Coast of the USA even more susceptible to this pathogen, in case of warmer temperatures during spring precipitations (Venette 2009). P. ramorum-inoculated branch cuttings of coast live oaks (Quercus agrifolia) developed larger lesions in spring, a result interpreted to suggest a role of synchronicity between host cambium activity and pathogen colonization rate (Dodd et al 2008). Such co-occurrences between host phenology and pathogen sporulation are likely to be affected by climate shifts (Donnelly et al 2011).…”
mentioning
confidence: 99%
“…This spike in coast live oak mortality is predicted to markedly lower its basal area in the studied forests. However other research documents a correlation between variation among trees in date of largest lesions and variation in timing of bud burst and cambial phenology (Dodd et al, 2008).…”
Section: Jung Et Al (2009) Write That Up To 2007 "Stem Infections Hamentioning
confidence: 99%